Improvement of Digital Technologies in Marketing Communications of Tourism and Hospitality Enterprises - HRISTOFOROVA, Irina Vladimirovna; SILCHEVA, Lyudmila Vladimirovna; ARKHIPOVA, Tatiana Nikolaevna; DEMENKOVA, Alexandra Borisovna; NIKOLSKAYA, Elena Yurievna (Journal of Environmental Management and Tourism, 2019)
The article is devoted to the improvement of marketing communications in tourism and hospitality enterprises. It has been established that digital technologies used in marketing communications of tourism and hospitality enterprises will, in the nearest future, aim to create new forms of interaction with the audience. It has been proved that the crowd marketing method within integrated marketing communications, which accomplishes tasks comprehensively, could be of help in this regard. It has been determined that for the improvement of efficiency of marketing communications in the tourism and hospitality industry, it is of vital importance to invest in new digital channels of communication with the current and potential clients, to form new forms of relations for the exploration of new possibilities, to offer generous benefits for the attraction of consumers and to create autonomous and network communities for the solidification of the brand.